Q10 Action-HD: a randomised, double-blind, placebo-controlled prospective crossover trial investigating the efficacy and safety of bupropion in Huntington's disease. (29th August 2012) - Gelderblom, H; Fischer, W; Landwehrmeyer, B; McLean, T; Reilmann, R; Saft, C; Süssmuth, S; Priller, J
Abstract : Background: Apathy is a common behavioural problem in Huntington's disease (HD), repeatedly ranked as one of the most pressing problems by EHDN investigators. It is defined as the primary absence of motivation, lack of initiative and drive, as well as emotional blunting. Apathy has been related to dysfunctions of frontal lobe areas receiving dopaminergic (DA) projections and thought to be involved in reward and motivation. Effects of DA are regulated by norepinephrine (NE) reuptake in the frontal cortex, which largely lacks DA transporters. Bupropion blocks NE and DA reuptake, hereby potentially increasing DA neurotransmission areas particularly relevant for the generation of apathy. Aims: To investigate the efficacy and safety of Bupropion in the treatment of apathy in HD. Methods: In a cross-over design, apathetic HD mutation carriers are randomised to receive either Bupropion 150/300 mg or placebo. Primary outcome parameter is change of apathy evaluation scale (AES) score as judged by a family member after 10 weeks of treatment. Secondary outcome parameters are change of AES score (clinician, study participant) as well as psychiatric, cognitive and motor symptoms, ADL and caregivers distress. In addition, change of DA-mediated ventral striatal and ventromedial prefrontal activation will be investigated in response to a reward paradigm as quantified by fMRI. Results: In a collaborative process between trial centres and EHDN, Action-HD was refined to a national trial, which has been actively recruiting patients from four major sites in Germany since May 2012. Preliminary longitudinal data suggested that the AES score allows for reliable quantification of apathy. Depression and co-medication with antipsychotics were rigorously excluded. A gambling paradigm was established, which reproducibly induces DA-mediated activation during reward anticipation. It was corrected for changes in vasoreactivity due to age, medication, adapted to chorea and successfully tested in 40 healthy individuals. Conclusion: Action-HD is the first multicenter investigator-initiated trial dealing with the symptomatic treatment of apathy in HD. The process of development, conduction and termination of this trial will help to define standards for conducting other investigator-initiated trials in HD. In addition, the results of this trial may help to develop an evidence-based therapy for one of the most debilitating neuropsychiatric symptoms in HD. Funding: This trial is supported by a grant from HSG/HSC, EHDN and Neurocure (DFG).